IL-17C Is a Mediator of Respiratory Epithelial Innate Immune Response - Pfeifer, Philipp; Voss, Meike; Wonnenberg, Bodo; Hellberg, Jan; Seiler, Frederik; Lepper, Philipp M.; Bischoff, Markus; Langer, Frank; Schäfers, Hans-Joachim; Menger, Michael D.; Bals, Robert; Beisswenger, Christoph (American journal of respiratory cell and molecular biology, 2013)
The IL-17 family of cytokines consists of at least six members (IL-17A to -F). IL-17 directly activates epithelial cells leading to the expression of inflammatory mediators and antimicrobial factors. Recent studies showed that IL-17C is expressed by epithelial cells. It was the purpose of this study to examine the expression of IL-17 family members in respiratory epithelial cells during bacterial infection. We show that common bacterial pathogens, such as Pseudomonas aeruginosa and Haemophilus influenzae, and ligands of Toll-like receptors 3 and 5 (flagellin, polyI:C) induced the expression and release of IL-17C in cultured human bronchial epithelial cells (HBECs). The expression of IL-17A, -B, -D, or -E was not induced by bacterial stimuli in HBECs. IL-17C enhanced inflammatory responses of respiratory epithelial cells infected with P. aeruginosa. Furthermore, we demonstrate that cigarette smoke suppressed the expression of IL-17C in HBECs in response to bacterial infection and in vivo in the upper airways of mice colonized with H. influenzae. IL-17C could also be detected in bronchial tissue of subjects with infection-related lung diseases. These data show that IL-17C is involved in the innate immune response of respiratory epithelial cells and is suppressed by cigarette smoke.